Espectrometria de massas com ionização paper spray: uma nova abordagem na solução de problemas forenses - Marina Jurisch Purri Miranda (2019)
Mass spectrometry is a powerful analytical tool consolidated in analyzes of the most diverse areas of research and application. The introduction of ambient ionization sources further disseminated the use of the technique, enabling rapid and simple analyzes of analytes presentin complex matrices, minimizing matrix effects and sample pretreatment steps. In this context, the potential of the paper spray ionization technique as an alternative to the methods traditionally employed for forensic analysis has been demonstrated in the literature since its introduction. However, nowadays, the implementation of methods that use this technique in the routine of laboratories is difficult, for only the manufacturer Thermo Scientific produces and commercializes PS-MS sources, limiting its use to their equipment. Thus, in this study, PS-MSwas successfully applied in three situations of forensic interest, i.e. document analysis, investigation of sports supplements and identification of drugs. Using a simple analytical procedure, the samples were solubilized or directly analyzed generating low noise spectrabesides intense and stable signals, showing its potential as an alternative to the techniques traditionally employed in the routine of forensic investigation laboratories. BCAA samples and thermogenic action products were analyzed for compliance between label and product. Signals corresponding to the branched-chain amino acids (leucine, isoleucine and valine) were detected in all BCAA supplements, while in thermogenics caffeine was present in all samples, two of which were not in agreement with the ingredients listed on their labels. The documentary investigation enabled the detection of fraud in written documents with erasable and non-erasable pens using ambient ionization techniques, i.e. EASI-MS, PS-MS and DESI-MSI. Each pen presented a different chemical profile, making it possible to distinguish them by visualinspection of the mass spectra. In all analyzed situations, the fraud is easily detected irrefutably. Finally, the PS-MS technique was implemented in the laboratory of chemical analysis of the Civil Police of Minas Gerais, constructing a source PS-MS compatible with the available massspectrometry equipment having its effectiveness proven with analyzes of cocaine samples seized in police operations detecting the protonated form of cocaine (m/z 304), as well as caffeine (m/z 195), phenacetin (m/z 180), levamisole (m/z 205) and lidocaine (m/z 235), demonstrating the potential of the technique in solving some problems of forensic interest.